First report of Pseudomonas marginalis causing tuber soft rot of potato in Iran - Simin Ghasemi; Pejman Khodaygan; Srđan G Aćimović; Esmaeil Basavand (Journal of Plant Protection Research)
In 2016, potato tuber soft rot symptoms were observed in major potato production fields in Jiroft county (southern Kerman province, Iran). Bacteria, which appeared as white to creamy colonies, were isolated from diseased tissues and shown to be pathogenic on potato tubers after inoculation and re-isolation of the isolates. Based on the assessment of colony morphology, biochemical characteristics, and analysis of 16S rRNA and gyrB gene sequences, the pathogen was identified as Pseudomonas marginalis. To our knowledge, this is the first report of P. marginalis causing potato tuber soft rot disease in Iran.